2020
DOI: 10.4995/muse.2020.12622
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Active Recreational Math Games on Math Anxiety and Performance in Primary School Children: An Experimental Study

Abstract: This study investigates the effect of active recreational maths games (ARMG) on 1st grade male students' maths anxiety and performance. The sample was divided into two groups: an experimental group (N=28), which was taught maths with ARMG in addition to traditional teaching methods, and a control group (N=30), which was taught with traditional teaching methods only. The ARMG consisted of 24 sessions taking place over a period of two months. Students participated in three sessions per week, each of which lasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
2
17
0
4
Order By: Relevance
“…According to the study, post -learning achievement was better than pre -learning achievement, with statistical significance at 0.01 (total score: 17.06), thus signifying better digital intelligence (average score increased to 7.16); this is in line with a study conducted by Lerdrungporn, P., Wattananarong, K., & Wiriyanon, (2017), which compared the learning achievement (average score) of students' learning with instructional management for touch-screen computers and students' learning with conventional methods using independent T-tests (two sample groups); the comparison showed statistically significant difference at 0.05; (Alanazi, 2020) thus, the T-test was feasible in the study.…”
Section: Discussionsupporting
confidence: 88%
“…According to the study, post -learning achievement was better than pre -learning achievement, with statistical significance at 0.01 (total score: 17.06), thus signifying better digital intelligence (average score increased to 7.16); this is in line with a study conducted by Lerdrungporn, P., Wattananarong, K., & Wiriyanon, (2017), which compared the learning achievement (average score) of students' learning with instructional management for touch-screen computers and students' learning with conventional methods using independent T-tests (two sample groups); the comparison showed statistically significant difference at 0.05; (Alanazi, 2020) thus, the T-test was feasible in the study.…”
Section: Discussionsupporting
confidence: 88%
“…The forest plot for the digital games interventions is shown in figure 3. Note how the heterogeneity was much lower than the one computing considering all the studies ( 2 = 68.8%), partially due to the removal of the outlier study by Alanazi (2020).…”
Section: Random-effects Model Meta-analysismentioning
confidence: 81%
“…Our leave-one-out sensitivity analysis showed how the results were robust: the overall effect size varied from −0.36 to −0.16 and only in 4 out of 16 cases the confidence level of the overall effect size was significant at 95% level. The value of −0.16 was obtained by removing the outlier study of Alanazi (2020). We also checked the sensitivity to − , the correlation between the pre-and post-test.…”
Section: Discussionmentioning
confidence: 99%
“…Recent comparisons between traditional teaching approaches and active recreational maths games (ARMG) have been trialled [26]. In this research, a sample of 60 first-grade Saudi Arabian primary school children (UK age 6-7 years) were randomly allocated to the control group (n=32) or experimental group that would participate in three weekly, 45-minute sessions (including counting, subtraction, additions, shapes) over a two-month period, and MA scores were determined using a translated 23-item iteration of the Mathematics Anxiety Scale for Children [27] [28].…”
Section: Interventions To Reduce Mamentioning
confidence: 99%
“…Nonetheless, studies that have implemented and reported targeted strategies appears to show a trend of reducing MA, andto an extentpromoting maths attainment. Alanazi [26] suggests that this may be associated with supporting self-concept, self-esteem [29], self-confidence and, crucially, self-efficacy [30]. Jansen and colleagues [31] manipulated perceived success rates on a computer-based maths task completed by primary school children (aged 6-10 years).…”
Section: Interventions To Reduce Mamentioning
confidence: 99%